Breeding Practices and Trait Preferences of Sheep Farmers in a Sub-Humid Tropical Environment - A. Yakubu; S. Isa; O. Alabi; A. J. Shoyombo; A. I. Adeolu (Faculty of Animal Science, Bogor Agricultural University, 2020)
The present study was carried out to determine the livestock breeding practices and the trait preferences of sheep farmers in Nasarawa State, Nigeria. A total of 132 sheep keepers were randomly sampled out of which data from 120 farmers were utilized in the final analysis. Primary data were collected through individual semi-structured questionnaire administration. Categorical and continuous variables including production and breeding traits were statistically tested based on sex of the respondents. Age of respondents, educational status, primary occupation, access to credit, and type of landholding were significantly different between the male and female farmers. Flock size was higher in farms owned by male farmers (19.63±1.04 versus 15.16±1.00). However, both sexes did not differ (p>0.05) in the ranking of meat, religion, income, hides, and skin and cultural purpose as reasons for keeping sheep. As regards management of sheep, control of breeding and access to veterinary services were low among female farmers. Apart from cultural/religious significance which was ranked higher by female farmers (63.38 versus 52.23; p≤0.05), other production traits such as disease resistance, survivability, growth rate, meat quality, fertility, body size, and prolificacy did not vary between sexes. Disease resistance, which the male farmers attached more importance (57.0 versus 70.52; p≤0.05), was the only significant breeding trait between sexes. Categorical principal component analysis (CATPCA) also revealed little influence of sex on the production and breeding traits investigated. The present findings could guide interventions such as the setting up of sustainable community-based breeding schemes to improve sheep production in the study area.